2016
DOI: 10.1111/jeu.12304
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Entamoeba polecki with Unique 18S rRNA Gene Sequences from Celebes Crested Macaques and Pigs in Tangkoko Nature Reserve, North Sulawesi, Indonesia

Abstract: Unique species of macaques are distributed across Sulawesi Island, Indonesia, and the details of Entamoeba infections in these macaques are unknown. A total of 77 stool samples from Celebes crested macaques (Macaca nigra) and 14 stool samples from pigs were collected in Tangkoko Nature Reserve, North Sulawesi, and the prevalence of Entamoeba infection was examined by PCR. Entamoeba polecki was detected in 97% of the macaques and all of the pigs, but no other Entamoeba species were found. The nucleotide sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Until very recently, ST4 had been detected only in human hosts. However, Tuda et al (21), found ST4 in 75 Celebes crested macaques (Macaca nigra) in Tangkoko, North Sulawesi, Indonesia. In that study, ST4 appeared to be a practically consistent finding in these animals, being detected in 97.4% of these monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until very recently, ST4 had been detected only in human hosts. However, Tuda et al (21), found ST4 in 75 Celebes crested macaques (Macaca nigra) in Tangkoko, North Sulawesi, Indonesia. In that study, ST4 appeared to be a practically consistent finding in these animals, being detected in 97.4% of these monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, ST4 appeared to be a practically consistent finding in these animals, being detected in 97.4% of these monkeys. Regarding the study by Tuda et al (21), it remains unclear whether all cases of ST4 were confirmed by sequencing or whether the subtype-specific PCR designed for the study (see above) was used diagnostically. Nevertheless, at least one sample from a crested macaque was identified molecularly as ST4 (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, E. polecki ST4 was only known from humans. Recently, however, ST4 was found in wild Celebes crested macaques ( Macaca nigra ) [20]. Although E. polecki is considered less pathogenic to humans or animals in the case of solo infection, coinfections with other pathogens, such as Lawsonia intracellularis , may increase the severity of the disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…E. suis is thought to induce hemorrhagic colitis by invading the lamina propria (Matsubayashi et al 2014). E. polecki ST1 and ST3 are associated with proliferative enteritis caused by Li (Matsubayashi et al 2015a(Matsubayashi et al , 2015b(Matsubayashi et al , 2016, although the ST2 and ST4 subtypes, which have been detected in humans and nonhuman primates (Jirků-Pomajbíková et al 2016, Tuda et al 2016, have not been reported in pigs. E. histolytica infection has only been observed in miniature pigs in an experimental setting, but never in farmed animals (He et al 2012).…”
Section: Introductionmentioning
confidence: 99%